Functional forms commonly used in CGE models - Femenia, Fabienne (International Food Policy Research Institute, 2012)
This technical note presents a review of the functional forms commonly used to represent demand and production in Computable General Equilibrium (CGE) models. The general properties of demand and production functions are described. The note also includes the detailed derivation of some specific functions.